Building a Model of the Influence of Information Technology Usage, Technology Competence, and Technostress on Lecturer Performance in the Digital Age - Kurniawan, Dian; Rinandiyana, Lucky Radi; Mufreni, Alfin Nurfahmi; Budiman, Asep; Kurniawati, Ane; Badriatin, Tine (Indonesian Journal of Social Science Research, 2024)
Universities must carry out digital transformation in the era of the Industrial Revolution 4.0 and Society 5.0. The application of infor-mation technology brings the hope of increasing lecturer performance and ultimately improving student quality. The use of information technology and lecturer technological competence will help achieve optimal performance. The demands of the application of information technology are thought to cause a new phenomenon known as "tech-nostress", which is the negative effects and stress triggers that arise from the use of technology in various areas of life, including the work-place. This study offers lecturer technological competence variables because they have an impact on the effectiveness of the use of infor-mation technology, so that the model built combines three important variables (use of information technology, technological competence, and technostress) to explain lecturer performance in the digital era. The study will use a quantitative survey approach to solve the prob-lem. Data were analyzed using the structural equation modeling (SEM) method to test the hypothesized relationship. The results showed that there was an influence of the use of digital technology on technostress, while digital competence had a negative influence on technostress. The technostress variable had a negative influence on lecturer performance. This study is expected to provide a better un-derstanding of how the use of information technology, technological competence, and technostress affect lecturer performance in the digi-tal era. Based on existing findings to reduce the impact of tech-nostress due to the use of digital technology, lecturers' ability to mas-ter technology must be improved. The model built can be a basis for further, more specific research, for example investigating the influ-ence of certain technologies on technostress or the moderating role of other supporting factors.